Serial FNA allows direct sampling of malignant and infiltrating immune cells in patients with B‐cell lymphoma receiving immunotherapy. Issue 3 (15th November 2021) - Mooney, Kelly L.; Czerwinski, Debra K.; Shree, Tanaya; Frank, Matthew J.; Haebe, Sarah; Martin, Brock A.; Testa, Stefano; Levy, Ronald; Long, Steven R.
Abstract : Background: Fine‐needle aspiration (FNA) is used to diagnose malignancies, recurrences, and metastases. The procedure is quick and well tolerated and can be facilitated by ultrasound guidance. Methods: This article describes the authors' experience in using serial FNA to harvest cellular material during 4 clinical trials of immunotherapy by in situ vaccination in patients with low‐grade lymphoma. Results: Two hundred ninety‐six FNA samples were collected from 44 patients over a span of approximately 6 weeks for each patient. Samples were sufficient in quantity and quality to be analyzed by flow cytometry and/or single‐cell messenger RNA sequencing. FNA samples yielded an average of 12 × 10 6 cells with a mean cellular viability of 86%. Material collected from the tumor lymph nodes differed significantly in the proportions and phenotypes of cellular populations in comparison with matched peripheral blood samples. A comparison of flow cytometry results obtained by FNA directly from the patient and by FNA performed ex vivo and a dissociation of the same lymph node after surgical excision confirmed that FNA sampling of the patient accurately represented the tumor and the microenvironment. An analysis of the FNA samples from immunotherapy‐treated target lymph nodes versus nodes from nontreated tumor sites provided insight into the impact of specific immunotherapy regimens. Conclusions: This is the largest study describing the use of serial FNA sampling to harvest cellular material during immunotherapy clinical trials. The success of this technique opens the door for FNA sampling to expand significantly future investigations of the dynamic effects of investigational agents, be they immunotherapies or targeted therapies. Abstract : Fine‐needle aspiration is a dependable method of collecting samples directly from multiple tumor nodules sequentially over the course of immunotherapy regimens. These cellular samples can then be studied and profiled to track patient responses to therapy and to study both the tumor and its microenvironment.